Analisis Karakteristik Ibu Terhadap Pengetahuan Tentang Pemberian MPASI Rumahan Dan MPASI Pabrikan Di Bidan Praktik Mandiri Di Wilayah Puskesmas Kotabaru Bekasi Barat - Endah Dian Marlina; Rosita Syaripah; Suci Sholihat (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Complementary food (MP-ASI) is very important for babies after the age of 6-24 months, because breast milk no longer provides the nutrients needed. In this case, the mother's knowledge of MP-ASI is very influential. The relationship between maternal characteristics and knowledge about providing MP-ASI includes maternal knowledge, maternal age, maternal education, maternal occupation and family income. The aim of the research is to analyze the relationship between maternal characteristics and knowledge about giving local breast milk and manufactured breast milk to babies aged 6 - 24 months in independent practice midwives in the working area of Kotabaru Health Center, Bekasi City in 2023. This research uses Observational Analytical research with a Cross-Sectional research design. The population in this study were mothers who had babies aged 6-24 months in Independent Practice Midwives in the Kotabaru Health Center Work Area, Bekasi City, totaling 99 respondents. The sample used was total sampling. The instrument used in this research is a structured interview which is guided by a checklist which has been tested with validity and reliability tests. The research results from a sample of 99 respondents showed that 70 respondents (70.7%) gave high levels of MP-ASI, 24 respondents (24.2%) gave moderate MP-ASI, and 5 respondents gave low levels of MP-ASI. respondents (5.1%). The chi square test with a significance level of 95% or ɑ = 0.05 obtained a value of p = 0.038 < 0.05. This shows that there is a relationship between maternal knowledge and the provision of MP-ASI to babies aged 6-24 months in independent practice midwives in the working area of Kotabaru Health Center, Bekasi City in 2023.